Teaching AI-Enhanced Environmental Technologies: A Pedagogical Framework for Integrating Deep Learning and Electrochemistry in STEM Education - Chtaini, Abdelilah (Journal of Pedagogy and Education Science, 2025)
This study presents an innovative pedagogical framework for teaching advanced environmental technologies by integrating artificial intelligence concepts with electrochemical systems in STEM education. We developed a comprehensive educational approach that uses AI-enhanced electrode systems for pollutant degradation to teach interdisciplinary concepts spanning chemistry, physics, computer science, and environmental engineering. The pedagogical model employs project-based learning (PBL), inquiry-based instruction, and hands-on experimentation to help students understand complex concepts, including convolutional neural networks (CNNs), electrochemical principles, and environmental remediation. Implementation across three educational levels (undergraduate, graduate, and professional development) demonstrated significant improvements in conceptual understanding (87% average improvement), interdisciplinary thinking skills (76% enhancement), and practical problem-solving abilities (92% improvement in project outcomes). The framework includes scaffolded learning modules, interactive simulations, and assessment rubrics to evaluate student comprehension of AI-electrochemical integration. This research contributes to STEM education by providing educators with a structured approach to teaching cutting-edge technologies while addressing real-world environmental challenges.